Practice Variations in the Use of Novel Oral Anticoagulants for Nonvalvular Atrial Fibrillation-Related Stroke among Stroke Neurologists in Saudi Arabia - Mohammed H. Alanazy; Taim Muayqil (Neurology Research International)
Clinical trials have demonstrated that novel oral anticoagulants (NOACs) are noninferior to warfarin in preventing nonvalvular atrial fibrillation- (nvAF-) related stroke and systemic embolism. However, in these trials, NOACs initiation was delayed for a variable period after stroke. Herein, we aimed to investigate the variability in early initiation of NOACs after nvAF-related stroke among stroke neurologists in Saudi Arabia. A standardized questionnaire was distributed electronically to all the stroke neurologists and fellows in Saudi Arabia. The questionnaire primarily focused on the timing of NOACs initiation after an nvAF-related stroke, according to stroke size (small, medium, and large) and location (anterior or posterior circulation). Thirty-six (85.7%) of the 42 stroke neurologists, who were contacted, participated in the survey. All participants would initiate NOACs in the first 3 days after a TIA; most of them initiate NOACs within 7 days after a small stroke, 4–14 days after a medium stroke, and ≥12 days after a large stroke, regardless of stroke location. Presence of a symptomatic intracranial hemorrhage further delayed initiation of NOACs. Additionally, 77.8% of the participants would bridge with antiplatelets before initiation of NOACs, and 55.6% would use a single antiplatelet agent. In conclusion, the practice of stroke neurologists is consistent with and supports the available evidence from observational studies on the time of initiation of NOACs. Our findings provide a guide for clinicians who manage nvAF-related stroke until more robust evidence from randomized controlled trials is available.